Demystifying Big Data: mandatory evolution for forensic accounting in Brazil. (29th February 2020) - Lima, Rafael Sousa; Serrano, André Luiz Marques; Cupertino, César Medeiros; Souza, Audrey Jones De; Ferreira, Lucas Oliveira Gomes
The objective of this study is to present both a theoretical and practical analysis about using the potentialities of Big Data in the combat financial crimes in Brazil. A direct documentary research was carried out. It analysed forensic reports elaborated by the National Institute of Criminalistics between the years of 2015 and 2017. It also conducted a bibliographical research regarding the current technological context. Conclusions indicate that the use of Big Data techniques increase effectiveness in tackling financial crimes and that the Cognitive Financial Analysis technique is the starting point in this technological evolution. Considering the unexplored potential of attacking corruption, it is necessary to demystify it, promoting the Data Analytics culture and supplying the lack of practical and active contribution of the academic community to solving one of society's biggest problems in Brazil.